THE APPLICATION OF THE GROUP DISCUSSION METHOD IN THE TEACHING WRITING DAILY ACTIVITY TEXT IN GRADE 7TH SMPN 3 KUTOREJO MOJOKERTO (RETAIN, 2015)
Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana penerapan metode group discussion dalam mengajar menulis dan mengetahui respon siswa setelah penerapan metode group discussion. Penelitian ini adalah penelitian deskriptif-kualitatif karena peneliti ingin menganalisa dan mendeskripsikan penerapan metode group discussion dalam pengajaran menulis. Subject penelitian ini adalag guru dan siswa kelas tujuh SMPN 3 Kutorejo Mojokerto. Observasi , interview dan catatan lapangan untuk mengumpulkan data. Hasil dari observasi yang dilakukan guru menerapkan metode group discussion dengan baik dan siswa memberikan respon yang yang baik selama penerapan metode group discussion. Kebanyakan siswa merasa gembira, termotivasi dan merasa terbantu dalam memahami materi yang disajikan Kata Kunci: Grup Diskusi, Menulis, Murid kelas tujuh Abstract The objectives of this research are to get know the implementation of the group discussion method in teaching writing and the students’ response after the implementation of the group discussion method in teaching writing. This research is a qualitative-descriptive research because the researcher wants to analyze and describe the the application of the group discussion method in teaching writing. The subject observed in this study was the English teacher and seventh grader SMPN 3 Kutorejo Mojokerto. The research instrument are an interview guide, observation sheets and field note . The observation result showed that the teacher implemented the group discussion well and students gives good responses throughout the implementation of group discussion method. Many students are happy, motivated, feels helped in understanding the material presented Keywords: group discussion, writing, seventh grade students.